2006
DOI: 10.1007/s00261-006-9046-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute adrenal hemorrhage after blunt trauma

Abstract: Information regarding the size of the hematoma and the presence of extravasation helps to select the appropriate management of patients with traumatic adrenal hemorrhage. TAE appears to be useful for treating patients with massive adrenal hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…[8][9][10][11][12] We applied angiography to 18 patients and performed embolizations in 4 of these patients. All patients receiving TAE for BAGT were alive and discharged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] We applied angiography to 18 patients and performed embolizations in 4 of these patients. All patients receiving TAE for BAGT were alive and discharged.…”
Section: Discussionmentioning
confidence: 99%
“…3,7 Transcatheter angiographic embolization (TAE) has become a well-established method of managing traumatic hemorrhage; however, there are a limited number of case reports on the benefits and effects of angiography in BAGT. [8][9][10][11][12] In the present study, we demonstrated the feasibility and safety of angiography for BAGT and analyzed the clinical presentation, incidence, management, and outcome of BAGT at a level I trauma center. Study population.…”
mentioning
confidence: 99%
“…We have found only one other case of a traumatic adrenal pseudoaneurysm in the literature, reported by Ikeda et al [6]. In that case, the patient became hypotensive 8 h postinjury.…”
Section: Discussionmentioning
confidence: 81%
“…CT angiogram after injury revealed a blush within his adrenal hematoma. The patient underwent successful embolization of his inferior adrenal artery [6].…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal haemorrhages occurred up to three days after injury (table 2); these have been reported to occur in up to 25% of severely injured patients (Ikeda et al 6). …”
Section: Resultsmentioning
confidence: 94%